Improving the monitoring of distribution of cyst nematodes - A. G. Babich; A. A. Babich (Российский паразитологический журнал, 2016)
Methods of monitoring of cyst nematodes using telecommunication technolo-gies, aerospace photography, as well as the traditional route investigation of agro-cenosis have been improved. Terms, sequence of monitoring implementation steps and perspectives of practical use of different cartograms of nematodosis have been proved. It is necessary to select and analyze plant samples on all four field sides. 5 plants from each sample are investigated on a rectangular field. In relation to culti-vated crops, perennial legumes – 100 plants from each field were studied. A me-chanic sampler device is being used for plant sampling that allows to reduce 10 times labor costs. Aerial photography of the earth surface including fields enables to detect the centres of plant infection. Aerospace monitoring of plant nematodosis is being conducted at the end of June – in the first and second decades of July. For more precise examination small aircraft and remote sensing unmanned planes with digital cameras are being used. Spectral analysis of pictures allows to detect nidi of plant damage by nematodes. To determine degree of plant damage and species composition of nematodes a route examination of fields are conducted, cartograms created, forecasts fulfilled, electronic cards of cyst nematode spread created.